PENDAMPINGAN KEMANDIRIAN PENYANDANG TUNAGRAHITA MELALUI KETERAMPILAN MEMASAK Di MADIUN - Supriyanti, Iin; Muttaqin, Nurul; Khumairo’ Al Manik, Siti; Qurrota A’yun, Neny (Institut Agama Islam Riyadlotul Mujahidin, 2024)
The mentally retarded person in this service is a woman and she wants to get married. The limitations of people with intellectual disabilities, which are accompanied by hearing and speech impairments, mean the need for skills to be taught as provisions for building a household. This research uses a descriptive method with a qualitative approach. The data used in this research is combined data, consisting of primary and secondary data, obtained through interviews and literature studies. This research aims to provide a real picture of assisting the skills of mentally retarded people through cooking activities. From the results of the service carried out, it shows that independent assistance for the mentally retarded in teaching cooking skills is enthusiastic, it is known that mentally retarded people can carry out the stages of mentoring cooking skills and run well.